Goosegrass and Bermudagrass Response to Rates and Tank Mixtures of Topramezone and Triclopyr. (16th August 2017) - Cox, Michael C.; Rana, Sandeep S.; Brewer, John R.; Askew, Shawn D.
Abstract : Postemergence herbicide options for mature goosegrass [ Eleusine indica (L.) Gaertn.] control in bermudagrass ( Cynodon spp. Rich.) turf are lacking. Greenhouse and field trials were conducted to determine the lowest rate at which topramezone, with or without triclopyr, controls goosegrass while maintaining acceptable bermudagrass quality. Greenhouse dose–response studies determined herbicide rates for field trials. In field trials, topramezone at 6.13 to 12.3 g a.i. ha −1 applied twice at a 3‐wk interval eliminated 8‐ to 18‐tiller goosegrass at three of four locations. The same topramezone treatments did not reduce smooth crabgrass [ Digitaria ischaemum (Schreb.) Schreb. ex Muhl.] cover more than 53% when applied alone and not more than 84% when applied with triclopyr at 140 g acid equivalent ha −1 . The number of days over a threshold of 30% injury or stunting (DOT30 ) within the 28‐d period following each of two herbicide treatments was calculated for 31 bermudagrass varieties. Bermudagrass injury DOT30 following the first treatment ranged from 11.1 to 17.8 d, depending on variety. The addition of triclopyr increased injury DOT30 but reduced the severity of discoloration by eliminating white tissue discoloration. All varieties were severely injured but completely or near completely recovered by 28 d after each treatment. Generally, topramezone at 6.13 or 12.3 g a.i. ha −1 applied twice controls goosegrass in bermudagrass. Addition of triclopyr improves smooth crabgrass control and decreases severity of bermudagrass injury but increases suprathreshold‐injury duration.